Estrés según factores ambientales en madres de recién nacido prematuro Hospital Regional Docente - Valdivia Gamarra, Gloria Janeth (2019)
The research study is quantitative, descriptive type was carried out during the months of September 2017 until February 2018, in the Neonatology service of the Trujillo Regional Teaching Hospital; with the objective of determining the level of stress in the mothers of premature newborns hospitalized in Neonatal Intensive Care. The sample universe was a total of 30 mothers as participants. For data collection, the “Stress level measurement scale according to environmental Factors” was used as an instrument. The research study concluded that, according to the subscales, the environmental factor that generates stress is found: first, the Relationship with the child and role of mothers (73.3%), followed by the appearance and conduct of the child (63.3%), conduct and communication with staff (53.3%) and aspects and sounds of the unit (50%).